Depositional model of a bioherm based on factor analysis: a case study in Western Beijing, China - Cheng, Hao; Jin, Zhenkui; Zhu, Rukai; Wang, Jinyi; Zhu, Xiaoer; Li, Baiqiang; Blaise Ketchaya, Yanick (Frontiers in Earth Science, 2024)
As an important type of microbial carbonate, the study of bioherm sedimentary models is of great significance to the exploration and development of carbonate rock. Bioherms from the Lower Zhangxia Formation of the Middle Cambrian Miaolingian were discovered in the Xiaweidian section of Western Hills, Beijing. The stratigraphic sequence from bottom to top consists of micritic oolitic limestones, flat-pebble conglomerates, laminated limestones (bioherm), shales, sparry oolitic limestones, and mud-ribboned limestones. This study uses a range of techniques to analyze the geochemistry of these rocks, including scanning electron microscopy (SEM), X-ray diffraction (XRD), carbon and oxygen isotope analysis, and major and trace element analysis. To ensure the accuracy of the results, factor analysis was used to screen the data and identify the elements that best represent the characteristics of the samples, obtaining the most reliable factors for analyzing the deposition environment and determining the deposition model. Through factor analysis, carbon and oxygen isotopes, Fe, Ti, Ni, and V were selected to reconstruct the paleoenvironment and deposition model. The results suggest that the Zhangxia Formation bioherm formed in the shallow-water environment of the open platform facies at the edge of the carbonate platform, which provides ideal conditions for the growth of microorganisms and the development of extensive bioherms during this time period. Subsequently, as water depth decreased and hydrodynamic and oxidative conditions intensified, the environment became unsuitable for microbial growth, leading to the cessation of bioherm development. This study confirms the effectiveness of numerical analysis methods in reconstructing bioherm deposition model and expands the application of these methods in carbonate studies.